MEASUREMENT AND CONTROL OF THE LOAD OF ENERGY DEVICES - Usmonov Shukurillo Yulbarsovich; Odilov Sanjarbek Sodiqjon ugli (Galaxy International Interdisciplinary Research Journal, 2023)
The efficient management of energy devices can be achieved through the use of appropriate measurement and control techniques. Measurement tools such as watt meters and power monitors can be utilized to accurately measure energy consumption, while control techniques like load shedding and time-of-use pricing can be implemented to regulate energy usage. With these techniques in place, energy efficiency can be promoted, and environmental impact can be reduced.